Effect of Virgin Coconut Oil in The Treatment of Leucorrhea Caused by Candida Albicans Infection on Pregnant Women at Hospitals in Padang - Putri Zelfitri Zen; Desmiwarti Desmiwarti; Sumaryati Syukur (Andalas Obstetrics And Gynecology Journal, 2021)
Introduction : According to WHO, the prevalence of reproductive health problems in women has reached 33% from all types of diseases. One of the most frequent reproductive health problems is fluor albus. The incidence of candidiasis in pregnant women has doubly increased, especially at third trimester, compared to women who were not pregnant. Candida should be considered a dangerous pathogen in early pregnancy.Objective : This study compared the number of colonies before and after the administration of virgin coconut oil (VCO) to address vaginal discharge caused by C. albicans infection in pregnant women.Material and methods : This is an experimental study on 36 pregnant women. Examination of fluor albus is done by applying vaginal swab before and after administration of 1 tablespoon of VCO orally three times a day dan 5cc of VCO was applied on the vagina and vulva for intervention group, meanwhile the control group was not given anything. Statistical analysis to test the significance is done by using T-test.Results : There was a difference on average number of colonies with higher number of colonies prior to administration (137.17 ± 16.35 vs 122.17 ± 14.42). The average number of colonies at the first examination was 96.06 ± 8.85 colonies and increased at the second examination to 112.89 ± 12.49 colonies.Conclusion : There was an effect of VCO administration on decreasing the number of colonies in the intervention group (p=0.000), while in control group, there was increasing average number of colonies in the second examination (p=0.000).Keywords: Candida albicans, fluor albus, pregnant women, virgin coconut oil